2005
DOI: 10.1016/j.gca.2005.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Sources, degassing, and contamination of CO2, H2O, He, Ne, and Ar in basaltic glasses from Kolbeinsey Ridge, North Atlantic

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 91 publications
5
34
0
Order By: Relevance
“…In this case, we can use the concentration of CO 2 and its d 13 C to model the initial CO 2 content of the melt phase and its degassing history (e.g., Macpherson and Mattey, 1994). However, as noted in Section 4.4, d 13 C d > d 13 C v , i.e., D-values are negative for most of the present sample suite, indicating that pure equilibrium degassing conditions assuming either batch equilibrium degassing (BED) or fractional equilibrium degassing (FED) modes alone do not provide an adequate description of gas loss from the samples (see also Shaw et al, 2004;Macpherson et al, 2005). This can be seen in Fig.…”
Section: Constraints On Co 2 Degassing: Glass Phase Datamentioning
confidence: 89%
See 1 more Smart Citation
“…In this case, we can use the concentration of CO 2 and its d 13 C to model the initial CO 2 content of the melt phase and its degassing history (e.g., Macpherson and Mattey, 1994). However, as noted in Section 4.4, d 13 C d > d 13 C v , i.e., D-values are negative for most of the present sample suite, indicating that pure equilibrium degassing conditions assuming either batch equilibrium degassing (BED) or fractional equilibrium degassing (FED) modes alone do not provide an adequate description of gas loss from the samples (see also Shaw et al, 2004;Macpherson et al, 2005). This can be seen in Fig.…”
Section: Constraints On Co 2 Degassing: Glass Phase Datamentioning
confidence: 89%
“…Helium isotopes were measured on a MAP 215-50 noble gas mass spectrometer following procedures and protocols described previously (e.g., Shaw et al, 2004;Macpherson et al, 2005). Vesicle-sited gases were liberated using an on-line crushing technique (Scarsi, 2000), and the released gases were purified using a combination of Ti and Zr-Al (SAES) getter pumps and charcoal/Al-frit traps held at liquid nitrogen temperature.…”
Section: Methodsmentioning
confidence: 99%
“…North of Iceland, Kolbeinsey Ridge basalts show a decrease in 87 Sr/ 86 Sr and 3 He/ 4 He ratios, and an increase in 143 Nd/ 144 Nd ratios, with increasing distance from Iceland. Notably, Pb isotopes show no such relationship and provide no evidence for systematic mixing between depleted asthenospheric mantle and Icelandic hotspot material (Mertz et al, 1991;Macpherson et al, 2005b). Furthermore, other studies have revealed that trace element and Sr-Nd-Pb-Hf isotope variations of Icelandic basalts can be attributed to chemical and isotopic heterogeneities within the mantle source itself, and that MORB-like mantle may not contribute significantly to the generation of Icelandic lavas Kerr et al, 1995;Thirlwall, 1995;Chauvel and Hémond, 2000;Kempton et al, 2000;Fitton et al, 2003;Thirlwall et al, 2004).…”
Section: Geologic Setting and Backgroundmentioning
confidence: 93%
“…Nevertheless, recent models of mantle prop up a well-homogenized MORB source which results from a entirely convecting mantle mass (Ballantine et al, 2002;Class and Goldstein, 2005). To account for the variable volatile ratios, contributions of fluids from the crust through which magmas rise towards the seafloor have been also proposed (Marty and Zimmermann, 1999;Marty et al, 2001;Shaw et al, 2004;Macpherson et al, 2005). Along mid-ocean ridges, magmas can in fact acquire volatiles from both hydrothermal mineralization and sea water circulating in oceanic crust (Kent et al, 1999).…”
Section: Relative and Absolute Abundancesmentioning
confidence: 99%
“…In contrast, recent studies on He isotopes support a mantle model where the entire mantle mass is in convection and is well represented by a homogeneous MORB source (Ballantine et al, 2002;Class and Goldstein, 2005). Coupled to the supposed differences in UM primary melts, processes involving contribution of volatiles from the crust through which magmas migrate have been also hypothesized to explain the changing noble gases-CO 2 -H 2 O systematics of submarine volcanism (Marty and Zimmermann, 1999;Marty et al, 2001;Shaw et al, 2004;Macpherson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%